Prepare to repair - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
There is room for importing appropriate tractors and farm equipment to meet the cultivation needs of Pacific Island countries, concluded participants at a regional workshop on Tractor operations, safely and maintenance . The event was organised...